HIV-1 induces the first signal to activate the NLRP3 inflammasome in monocyte-derived macrophages (2023)
Background/Aims: Inflammasomes are multimolecular complexes that regulate caspase-1. They act as sensors for endogenous and exogenous signals, and mediate the processing of pro-IL-1ß into its secreted, biologically active form. The NLRP3 inflammasome and IL-1ß are particularly interesting because they are required for efficient control of viral infections. Indeed, HIV-1 induces expression of NLRP3 and IL-1ß in healthy controls, but not in HIV-1-infected patients. Here we evaluate whether HIV-1 can induce activation of the NLRP3 inflammasome. Methods: Human primary monocyte-derived macrophages were infected with HIV-1 in the absence or presence of classical NLRP3 inflammasome activators, and IL-1ß release was assessed by ELISA. Results: HIV-1 initiates the priming signal for NLRP3 inflammasome activation through the NF-?B-associated pathway in human primary monocyte-derived macrophages. Furthermore, priming of NLRP3 activation in response to HIV-1 was independent of the viral envelope, since similar results were observed with HIV-1 and pseudotyped HIV-1 lacking the env gene. Conclusion: Our findings suggest that HIV-1 infection promotes IL-1ß secretion by inducing the first signal for NLRP3 inflammasome activation, a phenomenon that may contribute to AIDS progression. Copyright © 2013 S. Karger AG, Basel.